The Problem Based Learning (PBL) Model Improves Learning Outcomes for Class X Students at SMA Negeri 1 Kualuh Leidong - Yusna Arifin; Zarkasih; Lusianna Sirait, Sisca (Journal of General Education Science, 2024)
Many learning models are applied in schools to eliminate fatigue and improve students' self-quality. The Showing Module learning model which has a name, attributes, sentence structure, setting and culture is revelation learning, project-based learning, problem-based learning and demand learning. This article aims to find out how to apply the issue based learning model to the sub-subject matter of monetary problems/needs. Issue-based learning (PBL) has characteristics, for example learning begins by providing a problem, the problem has a setting with existing reality, students in groups succeed in finding problems and recognizing holes in their insight, learning and searching for related material. with this problem. themselves and report the answer to the problem, while the teacher completes other things to do. PBL consists of five stages, namely organizing students towards the material, coordinating students to pick them up, helping with independent and group exams, creating and introducing antiques (works) and displaying them, as well as explaining and assessing the critical thinking process.